Formation of the system of financial flows management of insurance companies - Kneysler, Olga (Skhid, 2015)
Relevance of the study is due to the need of development and implementation of the adequate methods of management of financial flows that affect not only the rhythm and guarantee of providing the financial resources of insurance defense, but also the financial stability of the state, its sustainable economic development and the general welfare. The purpose of the study is the systematization of theoretical and applied approaches to the formation of the system of financial flows management of insurance companies and the identifying the problems of their functioning by main activities. The theoretical and applied approaches to the formation of the system of insurer's financial flows management are investigated; the advantages and disadvantages of each of them are showed. We characterize the interaction of several relatively independent financial flows as the objects of management in the context of movement of financial resources of the insurance companies. It is noted that the management of the insurer's financial flows should be considered by taking into account the specificity of their movement according to the activities through a set of key components of financial management, such as accounting as analysis, planning and forecasting, optimization, control. Under the management of financial flows of the insurance company we should understand the system of principles and methods for developing and implementing the management decisions related to the formation and usage of the insurer's financial resources by different activities in order to achieve the effective management. The main directions of research in the context of the management of financial flows of the insurance company are determined, the problems are defined and their solutions in the context of the movement of financial resources by insurance, reinsurance, investing and financing activities are outlined.